Development of a single‐run analytical method for the detection of ten multiclass emerging contaminants in agricultural soil using an acetate‐buffered QuEChERS method coupled with LC–MS/MS. Issue 2 (14th December 2016) - Lee, Young‐Jun; Choi, Jeong‐Heui; Abd El‐Aty, A.M.; Chung, Hyung Suk; Lee, Han Sol; Kim, Sung‐Woo; Rahman, Md. Musfiqur; Park, Byung‐Jun; Kim, Jang‐Eok; Shin, Ho‐Chul; Shim, Jae‐Han
Abstract : This study was undertaken to develop and validate a single multiresidue method for the monitoring of ten multiclass emerging contaminants, viz. ceftiofur, clopidol, florfenicol, monensin, salinomycin, sulfamethazine, sulfathiazole, sulfamethoxazole, tiamulin, and tylosin in agricultural soil. Samples were extracted using an acetate‐buffered, modified quick, easy, cheap, effective, rugged, and safe method followed by liquid chromatography with tandem mass spectrometric analysis in positive ion mode. Separation on an Eclipse Plus C18 column was conducted in gradient elution mode using a mobile phase of methanol (A) and distilled water (B), each containing 0.1% formic acid and 5 mM ammonium formate. The linearity of the matrix‐matched calibrations, expressed as determination coefficients, was good, with R 2 ≥ 0.9908. The limits of quantification were in the range 0.05–10 μg/kg. Blank soil samples spiked with 4 × and 20 × the limit of quantification provided recovery rates of 60.2–120.3% (except sulfamethoxazole spiked at 4 × the limit of quantification, which gave 131.9%) with a relative standard deviation < 13% (except clopidol spiked at 20 × the limit of quantification, which gave 25.2%). This method was successfully applied to the monitoring of 51 field‐incurred agricultural loamy‐sand soil samples collected from 17 provincial areas throughout the Korean Peninsula. The detected and quantified drugs were clopidol (≤ 4.8 μg/kg), sulfathiazole (≤ 7.7 μg/kg), sulfamethazine (≤ 6.6 μg/kg), tiamulin (≤ 10.0 μg/kg), and tylosin (≤ 5.3 μg/kg). The developed method is simple and versatile, and can be used to monitor various classes of veterinary drugs in soil.